IOS 13 Programming with Swift 5 - Second Edition - Pichler, Gregor (Packt Publishing, 2020)
Unleash the power of Swift 5 in your applications About This Video Learn the most common tasks and techniques an iOS developer needs in his/her everyday life Build a beautiful burger-recipe app ready for the App Store Master the latest Apple technologies such as SwiftUI, Dark Mode, CloudKit, and more In Detail The iOS 13 SDK arrives as a major milestone in the evolution of the Swift language with new and interesting features for developers such as Dark Mode, Apple Sign-in, CloudKit, SwiftUI, UIKit, and more. If you're looking to get started with iOS 13 programming, unravel the potential of Swift 5, and publish your apps on the iPhone and iPad, then this is the right course for you. This course will be a perfect guide on your iOS journey; it will take you through the capabilities of iOS 13 and show you how to put its principles into action. It equips you to handle the most common tasks an iOS developer will deal with daily. We begin by creating a burger-recipe application and gradually add features to it as we move on. You will also learn how to build simple apps using SwiftUI and master iPadOS, which is specifically created for tablets. You will learn about the differences between UIKit and SwiftUI, and explore how SwiftUI handles the look-and-feel of different platforms such as iOS, iPadOS, and MacOS. By the end of the course, you will have built an appetizing burger-recipe applicaiton.
Online resource; Title from title screen (viewed March 31, 2020)
Keywords: Electronic videos